Aplicación tecnológica de arcillas (acopios) de la sucesión superior de la formación Cerro Largo, Buenos Aires, Argentina - Garrido, Liliana Beatriz (1996)
Based on mineralogical, physicochemical and technological characterization, the brownish and red clays of the upper pelitic succession of the Cerro Largo Formation, Sierras Bayas, Province of Buenos Aires, recently redefined as Olavarría Formation, composed of predominant illitic material, with impurities of quartz, calcite, siderite, hematite, goethite and pyrite, are suitable for red ceramic producís of low water absorption (15%). Preliminary controlled mixtures of the two varieties found (brownish and red), with different technological properties, constitute a better quality product than the ones obtained with the individual clays, wen with the addition of 3-5% bentonite.